Influence of flavivirus co‐circulation in serological diagnostics and surveillance: A model of study using West Nile, Usutu and Bagaza viruses. Issue 5 (28th June 2019) - Llorente, Francisco; García‐Irazábal, Alberto; Pérez‐Ramírez, Elisa; Cano‐Gómez, Cristina; Sarasa, Mathieu; Vázquez, Ana; Jiménez‐Clavero, Miguel Ángel
Abstract: This study aims at assessing the serological cross‐reactions existing between three mosquito‐borne flaviviruses with avian reservoirs co‐circulating in Europe: West Nile (WNV), Usutu (USUV) and Bagaza (BAGV). The study is useful for a better interpretation of serological results in diagnostics and surveillance. Serum samples obtained from a natural host, the red‐legged partridge ( Alectoris rufa ), experimentally infected with WNV, USUV or BAGV were analysed using two commercially available WNV competition ELISAs suitable for serological surveillance, and by the confirmatory virus neutralization test (VNT). The ELISAs examined showed different levels of specificity for WNV, as judged by cross‐reaction observed with the other flaviviruses. By VNT, virus‐specific antibodies were confirmed in 80%, 50% or 0% of sera from WNV‐, BAGV‐, or USUV‐inoculated birds, respectively. The results indicate how the co‐circulation of cross‐reacting flaviviruses may affect the outcomes of WNV serological surveillance when applying currently available serological tools. On the one hand, the choice of the ELISA test for antibody screening should consider the differences found in specificity, since one test is more specific for WNV while the other one is more suitable for detection of a broader range of flavivirus antibodies. On the other hand, besides corroborating that cross‐neutralization occurs between flaviviruses from different serocomplexes (WNV/USUV and BAGV), this study points out that cross‐neutralization between WNV and USUV is not symmetric, and reveals the difficulty to identify USUV infections serologically. This finding indicates that actual USUV infections might be underestimated in the current diagnostic schemes.